Multiple Myeloma - A New Era of Treatment Strategies - Podar, Klaus; Anderson, Kenneth C. (Bentham Science Publishers, 2012)
Multiple Myeloma (MM), the second most common blood cancer in adults, is a clonal plasma cell malignancy within the bone marrow characterized by osteolytic bone lesions, renal disease, and immunodeficiency. It is now well established that MM cell- induced disruption of the bone marrow homeostasis between the highly organized cellular and extracellular compartments supports MM cell proliferation, survival, migration, and drug resistance via activation of various signaling pathways. Based on this knowledge, the prototypic drugs thalidomide, bortezomib, and lenalidomide, which target both MM cell